2014
DOI: 10.1590/s0100-736x2014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Enterohemorrhagic Escherichia coli O157: H7 from healthy dairy cattle in Mid-West Brazil: occurrence and molecular characterization

Abstract: Pesq. Vet. Bras. 34(1):24-28, janeiro 2014 24 RESUMO.-[Escherichia coli enterohemorrágica O157: H7 em bovinos leiteiros saudáveis no Centro-Oeste do Brasil: ocorrência e caracterização molecular.] Escherichia coli enterohemorrágica (EHEC) sorotipo O157:H7 representa as principais cepas de E. coli produtoras de toxina Shiga (STEC) relatadas em grandes surtos e doenças graves, tais como colite hemorrágica (CH) e síndrome hemolí-tica urêmica (SHU), potencialmente letais. O objetivo deste estudo foi reportar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Studies by Ferreira et al (2014) and Freitas-Filho et al (2014) were pioneering in determining the prevalence of STEC and STEC/O157:H7 in healthy cattle in the State of Goiás, Brazil, while our study evaluated the virulence factors and antimicrobial resistance in STEC isolates obtained from healthy sheep in this State. On the contrary, Blanco et al (2003) found a higher prevalence of non-O157 STEC in sheep compared to cattle, where our study did not reveal the difference between sheep (78.3%) and cattle (72.7%) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Ferreira et al (2014) and Freitas-Filho et al (2014) were pioneering in determining the prevalence of STEC and STEC/O157:H7 in healthy cattle in the State of Goiás, Brazil, while our study evaluated the virulence factors and antimicrobial resistance in STEC isolates obtained from healthy sheep in this State. On the contrary, Blanco et al (2003) found a higher prevalence of non-O157 STEC in sheep compared to cattle, where our study did not reveal the difference between sheep (78.3%) and cattle (72.7%) .…”
Section: Discussionmentioning
confidence: 99%
“…The enterohemorrhagic hemolysin hlyA makes adherence possible for eae -negative strains. When both hlyA and eae genes are present, this is an indicator for increased pathogenicity [ 10 ]. In addition, 20% of the isolates harbored the eae gene in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Shiga toxins are a family of related toxins with two major groups, Shiga toxin 1 ( stx1 ) and Shiga toxin 2 ( stx2 ), expressed by genes considered to be horizontally acquired by bacteriophages, and are encoded by stx1 and stx2 genes, respectively [ 5 , 8 ]. In addition, enterohemolysin [ 9 ] and intimin [ 10 ], encoded by hlyA and eae genes, respectively, are another form of virulence factors of the bacteria [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…STEC frequencies in cattle ranging from 16·5 to 78·3% were reported from the Midwest region (Salvadori et al ; Ferreira et al , ) with the detection of serotypes O26:NM, O111:NM, O118:H14 and O118:H16 in eae ‐positive strains. In the Goiás State (GO), Freitas‐Filho et al () described a prevalence of 1·9% of O157:H7 STEC strains among healthy dairy calves and Santos et al () isolated the O26 and O113:H21 STEC strains in cattle at slaughterhouse in the Mato Grosso State (MT). Only few reports from swine are available.…”
Section: Occurrence Of Stec In Animalsmentioning
confidence: 99%
“…The O157:H7 STEC isolates from Brazil and other Latin American countries share several phenotypic and genotypic characteristics and the analysis of their genetic relatedness suggested the presence of a particular clone more related to human infections in Brazil, as well as a common origin for some strains isolated from different sources and countries (Guth et al ; Bastos et al ; Regua‐Mangia et al ; Freitas‐Filho et al ). Some Brazilian O157 strains isolated from cattle did not express Stx, including the strains isolated by Cerqueira et al (), while all Brazilian strains recovered from human disease do.…”
Section: Virulence Of Stec Isolated From Animalmentioning
confidence: 99%